Diclofenac Inhibits 27-hydroxycholesterol-induced Differentiation of Monocytic Cells into Mature Dendritic Cells - Son, Yonghae; Kim, Bo-Young; Park, Young Chul; Kim, Koanhoi (Immune network, 2017)
We investigated whether diclofenac could influence the development of antigen-presenting cells in an oxygenated cholesterol-rich environment by determining its effects on the 27-hydroxycholesterol (27OHChol)-induced differentiation of monocytic cells into mature dendritic cells (mDCs). Treatment of human THP-1 monocytic cells with diclofenac antagonized the effects of 27OHChol by attenuating dendrite formation and cell attachment and promoting endocytic function. Diclofenac inhibited the transcription and surface expression of the mDC markers of CD80, CD83, and CD88, and reduced the 27OHChol-induced elevation of surface levels of MHC class I and II molecules to the basal levels in a dose-dependent manner. It also reduced the expression of CD197, a molecule involved in DC homing and migration. These results indicate that diclofenac inhibits the differentiation of monocytic cells into mDCs, thereby potentially modulating adaptive immune responses in a milieu rich in cholesterol oxidation products.